IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2005.
DOI: 10.1109/aspaa.2005.1540220
|View full text |Cite
|
Sign up to set email alerts
|

Onset detection using comb filters

Abstract: A technique for detecting note onsets using FIR comb filters which have different filter delays is presented. The proposed onset detector focuses on the inharmonic characteristics of the onset component and the energy increases of the signal. Both properties are combined by utilizing FIR comb filters on a frame by frame basis in order to obtain an onset detection function, which is suitable for detecting slow onsets. The proposed approach improves upon existing methods in terms of the percentage of correct det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The most common form of preprocessing used for musical onset detection is sub-band or multi-band decomposition. Most of the studies using multi-band processing, approach the problem in a similar fashion: dividing the signal into sub-bands, estimating OSS for each sub-band, combining either at the OSS level or the onset decision level to achieve a final decision for the onsets [6]- [10]. It is reported that the robustness is improved by using such methodology [7].…”
mentioning
confidence: 99%
“…The most common form of preprocessing used for musical onset detection is sub-band or multi-band decomposition. Most of the studies using multi-band processing, approach the problem in a similar fashion: dividing the signal into sub-bands, estimating OSS for each sub-band, combining either at the OSS level or the onset decision level to achieve a final decision for the onsets [6]- [10]. It is reported that the robustness is improved by using such methodology [7].…”
mentioning
confidence: 99%
“…In contrast, the onset detection system presented in [8], denoted as ODCF, utilises the harmonicity changes of the signal by using a bank of FIR comb filters, which also have a harmonic type of magnitude response. The filterbank utilises 12 comb filters, which delays cover the 12 semitones of octave 4.…”
Section: Onset Detection Based On Comb Filters (Odcf)mentioning
confidence: 99%
“…FIR comb filters can be efficiently implemented in the time domain. Thus, the harmonicity measure of [8] applied to a signal x(n) by using a comb filter with delay D will be given by:…”
Section: Onset Detection Based On Comb Filters (Odcf)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], a comparison between the approach in [1] and the psychoacoustically motivated approaches in [12], [13] was performed. Finally, Gainza et al [15] employed FIR comb filters on a frame by frame basis combining the inharmonicity properties with the energy increases of the signal onset.…”
Section: Introductionmentioning
confidence: 99%